Pengaruh Budaya Korporat terhadap Kinerja Karyawan melalui Komitmen Karyawan dan Kepuasan Kerja Karyawan PT. Bank Pembangunan Daerah Kalimantan Selatan - Adwin Tista; Saladin Ghalib; Hairudinor Hairudinor (JURNAL BISNIS DAN PEMBANGUNAN, 2015)
The research objective is to prove the effect of 1). Budaya Corporate (X), Against the Employee Commitment (Z1), Job Satisfaction (Z2) and Employee Performance (Y2),2).Job Satisfaction (Z2) Agaiant Commitment (Z1) and EmployeePerformance (3).Employee Commitment (Z1) on employee performance (Y). The study population were all employees of the 100 people with a total sample of 94 employees chosen by proportional random sampling. Gathering data using questionnaires designed using a Likert scale levels 1-5. Analysis of data using the structural model SmartPLS.The test results prove 1).Corporate culture (X), a significant effect on Employee Commitment (Z1) and job satisfaction (Z2), with much influence respectively 38.95% and 48.82%, but no significant effect on employee performance (Y2) with the influence 6.7%. 2).Job Satisfaction (Z2) significantly affects Employee l Commitment (Z1) with a 38.67% and did not influence significantly influence employee performance (Y) with great effect (-13.55%), 3). Employee Commitment (Z1) Significantly the Employee Performance (Y) with the influence 56.72%.Keywords:Corporate Culture, Employee Commitment, Job SatisfactionAnd Employee Performance